Spider-Web of Civilization: The Integrative–Interconnective Paradigm of Islamic Education in the Thought of Muhammad Amin Abdullah - Ngatmin Abbas; Khafidoh; Muhammad Umar Al Faroq; Abdullah; Ahmadi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Contemporary Islamic education faces a persistent epistemological challenge caused by the dichotomy between religious sciences and modern sciences. This separation limits its capacity to respond to complex civilizational issues that require textual understanding, empirical inquiry, social analysis, and philosophical reflection. This study aims to analyze M. Amin Abdullah’s integrative-interconnective paradigm by positioning the spider web metaphor as a conceptual framework for reconstructing Islamic education and strengthening its contribution to contemporary Islamic civilization. Using a qualitative library research design, this study examined Abdullah’s major work on integrative-interconnective Islamic studies as the primary corpus, supported by his other writings and relevant scholarly literature on Islamic education, epistemology, knowledge integration, and civilizational renewal. Data were collected through documentation and critical literature review, then analyzed using content analysis and conceptual analysis. The findings show that the integrative-interconnective paradigm reframes the dichotomy of knowledge as an epistemological problem rather than merely a curricular issue. The spider web metaphor presents knowledge as a relational network in which religious sciences, social sciences, humanities, natural sciences, and philosophy interact dialogically. The study further identifies hadārat al-nass, hadārat al-‘ilm, and hadārat al-falsafah as mutually corrective domains that integrate textual authority, empirical inquiry, and critical reflection. Through conceptual synthesis, this study extends Abdullah’s paradigm from an epistemological model into a civilizational framework for Islamic education. It concludes that the spider web paradigm provides a strong foundation for curriculum reconstruction, interdisciplinary learning, research culture, institutional transformation, and the formation of a knowledge-based Islamic civilization.